Assessment of the MP2 method, along with several basis sets, for the computation of interaction energies of biologically relevant hydrogen bonded and dispersion bound complexes - Riley, Kevin E; Hobza, Pavel (The journal of physical chemistry. A, 2007)
In the past several years the MP2 method has been used extensively in studies of noncovalent interactions within biological systems such as proteins, DNA/RNA, and protein-ligand complexes. In this work we assess the performance that can be expected of this method, when paired with several different medium and extended basis sets, for the accurate computation of binding energies of hydrogen bonded and dispersion bound biologically derived complexes. It is found that, overall, the MP2/cc-pVTZ method produces the best, most well balanced, description of noncovalent interactions. Another interesting observation made in this study is that generally the MP2 technique, when paired with any basis set, does not yield reliable results for cyclic hydrogen bonds such as those found in nucleic acid base pairs.
Keywords: DNA; proteiny; vodíková vazba; RNA; Hydrogen Bonding; Proteins